Gädlä Bǝsṭawros - Tefera, Amsalu (Aethiopica, 2010)
Bǝsṭawros was one of the famous abbots of Däbrä Ḥayq. He passed away at Gondär during the time of Iyasu II (1730-1755 A.D.) and his relics were taken to Däbrä Ḥayq some years after his death (Raineri 2003:549). He copied and caused to copy several manuscripts (for instance EMMLs nos. 1836, 2059, 2060 etc.) and donated to different churches. His Gädl is the primary source for his biography and was composed at 1894 A.D. The Gädl has various important aspects. It deals with various historical events and discusses theological controversies that took place in Ethiopia. This article is intended to present an edition and translation of Gädlä Bǝsṭawros.